2015
DOI: 10.1159/000374107
|View full text |Cite
|
Sign up to set email alerts
|

Human Umbilical Cord Blood Cells Ameliorate Motor Deficits in Rabbits in a Cerebral Palsy Model

Abstract: Cerebral palsy (CP) has a significant impact on both patients and society, but therapy is limited. Human umbilical cord blood cells (HUCBC), containing various stem and progenitor cells, have been used to treat various brain genetic conditions. In small animal experiments, HUCBC have improved outcomes after hypoxic-ischemic (HI) injury. Clinical trials using HUCBC are underway, testing feasibility, safety and efficacy for neonatal injury as well as CP. We tested HUCBC therapy in a validated rabbit model of CP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 55 publications
0
42
0
1
Order By: Relevance
“…Scores above 80 are classified using approximately the same ranges as IQ tests. Scores below 80 are categorized as borderline adaptive functioning (70-80); mildly deficient adaptive functioning (51-69); moderately deficient adaptive behavior (36-50); severely deficient adaptive behavior; (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35); and markedly or profoundly deficient adaptive behavior (<20) [44]. (c) Clinical Global Impression (CGI) subscales for Social, Receptive, and Expressive skills as rated by the PI based on clinical impressions.…”
Section: Endpoint Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Scores above 80 are classified using approximately the same ranges as IQ tests. Scores below 80 are categorized as borderline adaptive functioning (70-80); mildly deficient adaptive functioning (51-69); moderately deficient adaptive behavior (36-50); severely deficient adaptive behavior; (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35); and markedly or profoundly deficient adaptive behavior (<20) [44]. (c) Clinical Global Impression (CGI) subscales for Social, Receptive, and Expressive skills as rated by the PI based on clinical impressions.…”
Section: Endpoint Testingmentioning
confidence: 99%
“…Umbilical cord tissue and UCB have also been used to regulate immune dysfunction [31]. Preclinical studies have reported that cells from intravenously infused human UCB can migrate to the parenchyma of injured brain and alleviate neurological impairment in animal models of perinatal brain injury [32][33][34]. The demonstrated functional improvements were not due to cell differentiation and repopulation, but rather are hypothesized to be a transient paracrine effect of the infused cells upon the host cells.…”
Section: Introductionmentioning
confidence: 99%
“…Some UCB‐SCs likely differentiate into “replacement” glial cells and neurons and integrate into the host brain where they play a role in re‐myelination (Sato et al, ; Shen et al, ). In addition, UCB‐SCs might enhance blood vessel regeneration (Kourembanas, ), and an increasing number of studies have indicated that UCB‐SCs migrating to the site of brain injury might provide restorative and neuroprotective factors or endogenous cell signals to injured host neural cells via the paracrine activity of immune factors, anti‐inflammatory cytokines such as IL‐8 and IL‐10 (Nazmi et al, ; Xia et al, ), and neurotrophic factors such as neurotrophin‐3/4, brain‐derived neurotrophic factors, glial‐derived neurotrophic factor, vascular endothelial growth factor, hepatocyte growth factor, and insulin‐like growth factor‐1, which support neuronal migration, proliferation, and differentiation and promote angiogenesis (Bennet et al, ; Drobyshevsky et al, ; Geisler, Dinse, Neuhoff, Kreikemeier, & Meier, ; Hellstrom et al, ; Rosenkranz & Meier, ). UCB‐SCs act as a vehicle to deliver these factors or signals to injured tissues in a targeted way, thus reinforcing the survival potential of host cells and preventing cell death (Ko et al, ; Li et al, ; Liu, Sun, Gong, & Wang, ).…”
Section: Mechanisms Of Ucb‐sc Therapymentioning
confidence: 99%
“…The old concept that neuroregeneration does not occur in the central nervous system has been challenged by many workers both in animal and human experiments (12).…”
Section: Introductionmentioning
confidence: 99%